PENDAMPINGAN PENGELOLAAN ANGGARAN KEUANGAN DAN ASET SD MUHAMMADIYAH 08 DAN SMP 06 DAU - Setu Setyawan; Ahmad Juanda (Universitas Muhammadiyah Malang, 2020)
The community outreach that will be carried out to strengthen the Management of Financial and Asset Management Budget of SD Muhammadiyah 08 and SMP 06 Dau which are accountable for the charity business of the Malang Regional Muhammadiyah Persyarikatan in the field of education. level of performance in certain periods. So far, SD Muhammadyah 08 and SMP Muhammadiyah 06 Dau have not been maximized in reporting financial management, especially reporting fixed assets that are managed. The purpose of this program is to explore the potential sources of potential funds and then prepare a budget that is able to measure the level of performance in certain periods. While the assistance is carried out to create an accountable financial management system using the principles of Good Governance (good financial governance). The method used in the service program using the RAD (Rapid Application Development) method. The results of the training on Management of Financial and Asset Budget Management were very satisfying. This was shown by the results of the pre-test of 12 participants 4 people with a value of 25. 3 participants with a value of 50, 3 participants with a value of 60 and the remaining 2 participants received a value of 70. After being given the concept of the budget and performance-based training is then performed post-test the average value of participants in 80.